1999
DOI: 10.1161/01.hyp.33.2.647
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Coffee Drinking on Blood Pressure

Abstract: Abstract-We sought to assess the effect of coffee consumption on blood pressure in humans. Our data sources included a MEDLINE search of the literature published before December 1997, bibliography review, and expert consultation. We selected controlled trials in which coffee consumption was the only difference between the intervention and control groups, mean blood pressure change was reported for each group or period, and treatment lasted for Ͼ24 hours. Of 36 studies initially identified, 11 (522 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
151
1
14

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(170 citation statements)
references
References 50 publications
(55 reference statements)
4
151
1
14
Order By: Relevance
“…Human intervention studies have explored only the short-term effects of coffee consumption on precursors of CVD. Two meta-analyses of RCT on blood pressure (34,35) agreed that coffee consumption can increase blood pressure slightly. Another meta-analysis of fourteen intervention trials showed a significant dose-response relationship between coffee consumption and total or LDL cholesterol levels (36) .…”
Section: Cvdmentioning
confidence: 99%
“…Human intervention studies have explored only the short-term effects of coffee consumption on precursors of CVD. Two meta-analyses of RCT on blood pressure (34,35) agreed that coffee consumption can increase blood pressure slightly. Another meta-analysis of fourteen intervention trials showed a significant dose-response relationship between coffee consumption and total or LDL cholesterol levels (36) .…”
Section: Cvdmentioning
confidence: 99%
“…Studies which compared caffeine tablets with decaffeinated coffee were excluded. According to the meta-analysis, systolic and diastolic blood pressure increased by 0.8 mmHg (P`0.001) and 0.5 mmHg (P`0.01), respectively, for every cup of coffee during long-term coffee consumption (Jee et al, 1999).…”
Section: Acute Intake Of Coffee or Caffeine And Blood Pressurementioning
confidence: 99%
“…A recent meta-analysis of 11 controlled clinical trial with 522 participants assessed the effect of coffee intake on blood pressure by comparing the coffee group with the nocoffee control group (Jee et al, 1999). Studies which compared caffeine tablets with decaffeinated coffee were excluded.…”
Section: Acute Intake Of Coffee or Caffeine And Blood Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…In an analysis of 11 trials, the BP effects of coffee were estimated as 2.4 and 1.2 mm Hg for systolic and diastolic BP, respectively, compared with the non-coffee groups, 6 which contrasts with smaller effects of 1.22 and 0.49 mm Hg in a larger meta-analysis of 16 studies. 7 The mean treatment duration was similar in both analyses, although mean caffeine dosage was higher in the earlier study 6 (see Table 1), which may explain the discrepancy in effect size. Hypertensive status, genetic vulnerability to hypertension and interactions with smoking and mental stress may also be important.…”
mentioning
confidence: 89%